Capacity and Perfomance Evaluation of Drainage Channel (Case Study on Letjen Sutoyo Street Malang City) - Efendi, Medi; Harifa, Ayisya Cindy; Sutikno, Sutikno (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2022)
The channel along Jalan Letjen Sutoyo is a drainage channel that drains dirty water from the residential area of 0.65 km2. By evaluating the capacity and flow profile using the Storm Water Management Model (SWMM), it is hoped that flooding problems in the channel can be minimized. The capacity of the existing canal along Jalan Letjen Sutoyo is to accommodate a discharge of 13.62 to 29.09 m3/s so that we get the dimensions of a trapezoidal channel with a base width of 2.8 m with a height of 2.3 m at the beginning of the channel and becomes more extensive, namely a base width of 4 m with a height of 3.7 m. Enough capacity to accommodate a discharge of 29.09 m3/s. After the evaluation, it was found that there was accumulation at two points, namely J2 and J5, due to the maximum discharge added to the discharge from local settlements at that point. So it is necessary to redesign the channel to accommodate the discharge from the settlement. The redesign was only carried out by increasing the height of the channel to 5 m because increasing the width of the channel was not possible because the channel is in a densely populated area.ABSTRAKSaluran di sepanjang Jalan Letjen Sutoyo merupakan saluran drainase yang mengalirkan debit air kotor dari daerah Kawasan permukiman seluas 0,65 km2. Dengan membuat evaluasi pada kapasitas dan profil aliran dengan menggunakan Storm Water Management Model (SWMM) diharapkan permasalahan banjir pada saluran tersebut dapat diminimalisir.  Kapasitas saluran eksisting sepanjang Jalan Letjen Sutoyo adalah untuk menampung debit 13,62 hingga 29,09 m3/dt. Sehingga didapatkan dimensi berupa saluran trapesium dengan lebar dasar 2,8 m dengan ketinggian 2,3 m di awal saluran dan menjadi lebih besar yaitu lebar dasar 4 m dengan ketinggian 3.7 m. Kapasitas yang cukup untuk menampung debit sebesar 29,09 m3/dt. Setelah di evaluasi maka ditemukan adanya penumpukan pada dua titik yaitu J2 dan J5, akibat debit maksimum ditambahkan dengan debit yang berasal dari pemukiman setempat pada titik tersebut. Sehingga perlu adanya redesain saluran agar dapat menampung debit dari pemukiman. Redesain hanya dilakukan dengan penambahan ketinggian saluran menjadi 5 m, karena untuk penambahan lebar saluran tidak memungkinkan, karena saluran berada di wilayah padat pemukiman.